2018
DOI: 10.1186/s13041-018-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity changes in forebrain activity and functional connectivity during neuropathic pain development in rats with sciatic spared nerve injury

Abstract: Neuropathic pain is a major worldwide health problem. Although central sensitization has been reported in well-established neuropathic conditions, information on the acute brain activation patterns in response to peripheral nerve injury is lacking. This study first mapped the brain activity in rats immediately following spared nerve injury (SNI) of the sciatic nerve. Using blood-oxygenation-level-dependent functional magnetic resonance imaging (BOLD-fMRI), we observed sustained activation in the bilateral insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 87 publications
2
48
1
5
Order By: Relevance
“…In addition to pain sensory symptoms, the neuro-psychological functioning is affected by SNI, and the complex forebrain network is considered the substrate for negative affective states and cognitive impairments [9,14,15]. Behavioral modifications are associated with a maladaptive reorganization of the nervous system due to the changes in neurotransmitter release and neuronal firing activity at spinal and supraspinal levels in which neuron-glia cells communication takes place [16]. Indeed, it is accepted that SNI-mediated pain development is triggered by the activation of glia cells, microglia (early) and astrocytes (late), contributing to the neuronal sensitization at spinal cord level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pain sensory symptoms, the neuro-psychological functioning is affected by SNI, and the complex forebrain network is considered the substrate for negative affective states and cognitive impairments [9,14,15]. Behavioral modifications are associated with a maladaptive reorganization of the nervous system due to the changes in neurotransmitter release and neuronal firing activity at spinal and supraspinal levels in which neuron-glia cells communication takes place [16]. Indeed, it is accepted that SNI-mediated pain development is triggered by the activation of glia cells, microglia (early) and astrocytes (late), contributing to the neuronal sensitization at spinal cord level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that chronic pain can lead to over-excitation of neurons in different brain regions. These brain areas included spinal cord, thalamus, amygdala, anterior cingulate cortex, and others [15][16][17][18]. The thalamus is a gateway for relaying sensory signals to other cortical areas, such as the primary somatosensory cortex and secondary somatosensory cortex [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our novel finding was that more functional connectivity enhancement was observed between the hypothalamus, amygdala and thalamus at the early post-injury time point in CCI rats, when neuralgia sensitivity was at its peak. Some studies have found that the noxious stimulation of the sciatic nerve in rats might induce medial thalamus and hypothalamus activation during fMRI [16].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the limbic system not only served the integration of receiving the signals from S1 but also continuously exerted influence on S1 during treatment of electroacupuncture. The active regions with brachial plexus pain spatially overlapped with brain areas implicated in cognitive impairment in neuropathic pain [32][33][34][35]. Pain was considered multidimensional and produced by distributed neural patterns [7,36].…”
Section: Discussionmentioning
confidence: 99%